An evaluation of the environmental impact assessment practice in Uganda: challenges and opportunities for achieving sustainable development - Taako, Edema George; Kiemo, Karatu; Andama, Edward (Heliyon, 2020)
Environmental Impact Assessment (EIA) is a broad process that emerged from the National Environment Policy Act, 1970 in the U.S. Its primary objective is to generate information on the likely impacts of a project on all aspects of the environment and used in agency decision making and in the long run protect the environment and achieve sustainable development. EIA practice in Uganda was formally established through the National Environment Act, 1995 and now in practice for over 25 years. However, there is increasing level of water pollution especially Lake Victoria, rivers, streams, aquifers and soils. This research reviewed the institutional, legal and regulatory framework for EIA, related literature and EIA documents especially EIA reports and conducted key EIA stakeholders survey using questionnaires to identify capacity and practice issues. The results revealed that, there was gap between law and practice arising from inadequate and ineffective public participation, weak follow-up, low key stakeholder's capacity, political interference, lack of SEA practice and not embracing EIA in a transboundary context. However, there is fairly good and comprehensive institutional, legislative and regulatory framework for EIA, good local governance structures, adequate staffing, robust national planning framework, active non-state actors and regional groupings. In order to maximize the potential of EIA as a means for achieving the SDGs, we recommended measures to address the challenges facing the EIA practice as well as utilize the existing opportunities within the context in which EIA is applied.